Climate change symposium sur de changement climatique 2011 (2011)
That climate change, global warning and their consequences are already upon mankind and his environment is a fact that is not in doubt. Sadly enough, the impact of the climate change is more pronounced in african than any other continent due to lack of both short and long term adaptation policies and strategies that could be adopted to combact this threat. Should African not be able to respond to the changing climate, agricultural productivity which provides a means of livehood for about 70% of the African population would suffer serious devastating effects among which are reduction in crop yields and agricultural productivity, increased incidence of pest attacks due to an increase in temperature which favours insect growth, reduction in the amount of wter available in most part of African, longer drought periods, reduced soil fertility and poor livestock productivity. A viable adaptation strategy for enhancing agricultural productivity and preparing farmers for the effect of climate change in african is "Controlled Environment Agriculture (CEA)/Greenhouse Engineering" This is because CEA can be practiced as a low carbon and climate compatible way of agricultural production by using renewable energy. Unlike most other continent, African lags terribly behind in developing research capabilities as well as good policy formulation and implementation fir large scale agricultural production through CEA. Rain -fed/seasonal farming is still predominat while some other african nations depends largely on food aid from developed countries. CEA offers the possibility of mutiple harvest of crops in successive cycles as there is no need to wait for certain seasons before cultivation can be done. Should the african continent embrace en- mass, the technology behind CEA, the populace would stand a good chance of being nutritional food secured and in addition, mitigate the negative effects of climate change on agriculture by agriculture.